The Chirostyloidea of the Northeastern Pacific: Host Associations, Range Extensions and a New Species (Decapoda: Anomura) - Wicksten, Mary K.; Conway, Kevin W. (Zootaxa, 2023)
Four species of chirostyloid squat lobsters, including a new species and a range extension are reported herein from California. Uroptychus nicoleae sp.nov. was collected on a black coral, Lillipathes sp. off San Clemente Island. It is characterized by a rostrum bearing 1 or 2 lateral teeth, the carapace having 5 lateral spines and a belt of 15 spinules on the anterior dorsal surface, and the dactyls of pereopods 2–5 are curved and bearing a continuous row of 6–8 teeth. The new species is morphologically similar to U. bellus of the southwestern Pacific. The color in life is red and pink. Uroptychus occidentalis is reported for the first time off California. The chirostyloids Sternostylus iaspis and S. perarmatus, which also occur off California, are shown in video still images from a remotely operated vehicle. They inhabit antipatharians and soft corals (Primnoidae) and are easily distinguished from species of Uroptychus by their elongate chelipeds and spinose carapaces. We provide northern range extensions for Uroptychus bellus, Sternostylus defensus and Heteroptychus galapagos collected off Costa Rica.